Introduction to film analysis : technique and meaning in narrative film - Ryan, Michael; Lenos, Melissa (London Bloomsbury, 2020)
"This updated textbook provides students with instruction in how to analyze film images for the meanings they contain"--
Introduction -- Technique and meaning -- Close viewing -- Critical analysis.
Includes bibliographical references and index.
Keywords: Film criticism; Motion pictures